The Urgency of Establishing AI Regulations to Ensure Legal Certainty and AI Ethics in Responding to Challenges Digitalization in Indonesia - Saiful Ahmad, Ahluddin; Hana Santoso, Kamelia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of artificial intelligence (AI) technology in Indonesia has had a significant impact on various aspects of life, including the legal realm and the protection of individual rights. Phenomena such as deepfakes and generative AI, as seen in the case of the